The Gap to Involve the Banking Cheques into Green Banking: Review and comparison about the contribution of Electronic Clearing Cheque System, Remote Cheque Deposit Service and Electronic Cheque Service in the Green Banking - Mowaffaq Ayed Madarmeh, Rawan (International Journal of Engineering and Technology, 2018)
Green banking is going to lead the banking sector into 21st century, which is much needed in saving the world. The purpose of this paper is to address the gap in involving the banking cheques into green banking, by spotting the light on the environmental practices which are applied in Electronic Clearing Cheque System (ECCS), Remote Cheque Deposit Service (RCD) and Electronic Cheque Service (ECS) and the gaps in each. To achieve the purpose reviews and comparison in different aspects have been done which are related to ECCS, RCD and ECS. In addition, to guide the argument about the fact behind the death of paper cheques, especially after launching ECS which changed the direction of this argument. The findings could be used to help the banking in cheques field to go greener through focusing on investing in electronic cheque payment methods and improve the electronic cheque capabilities in the banking sector. Â Â Â